Tax Identification Socialization Media Application Ã¢â‚¬Å“Aku Tau Pajak SekarangÃ¢â‚¬Â Based on Android - Mentari, Mentari; Mulwinda, Anggraini (Universitas Negeri Semarang, 2020)
Socialization in the form of games or educational games will be more interesting and fun. In addition, the use of applications on smartphones can indeed be a practical alternative to increase the ability to adapt to the surrounding environment and current developments. The purpose of this research is to build a tax introduction application